Design of Perovskite Oxides as Anion-Intercalation-Type Electrodes for Supercapacitors: Cation Leaching Effect - Liu, Y.; Dinh, J.; Tade, M.; Shao, Zongping (American Chemical Society, 2016)
© 2016 American Chemical Society.Oxygen ions can be exploited as a charge carrier to effectively realize a new type of anion-intercalation supercapacitor. In this study, to get some useful guidelines for future materials development, we comparatively studied SrCoO3-d (SC), Ba0.5Sr0.5Co0.8Fe0.2O3-d (BSCF), and Co3O4 as electrodes in supercapacitors with aqueous alkaline electrolyte. The effect of interaction between the electrode materials with the alkaline solution was focused on the structure and specific surface area of the electrode material, and ultimately the electrochemical performance was emphasized. Both BSCF and SC were found to experience cation leaching in alkaline solution, resulting in an increase in the specific surface area of the material, but overleaching caused the damage of perovskite structure of BSCF. Barium leaching was more serious than strontium, and the cation leaching was component dependent. Although high initial capacitance was achieved for BSCF, it was not a good candidate as intercalation-type electrode for supercapacitor because of poor cycling stability from serious Ba2+ and Sr2+ leaching. Instead, SC was a favorable electrode candidate for practical use in supercapacitors due to its high capacity and proper cation leaching capacity, which brought beneficial effect on cycling stability. It is suggested that cation leaching effect should be seriously considered in the development of new perovskite materials as electrodes for supercapacitors.